2014
DOI: 10.1371/journal.pone.0106708
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Salmonella Serogroup-C1-Specific Gene Abrogates O7-Antigen Biosynthesis and Triggers NaCl-Dependent Motility Deficiency

Abstract: Several molecular detection marker genes specific for a number of individual Salmonella serogroups have been recently identified in our lab by comparative genomics for the genotyping of diverse serogroups. To further understand the correlation between serotype and genotype, the function of a Salmonella serogroup-C1-specific gene (SC_2092) was analyzed in this study. It was indicated from the topological prediction using the deduced amino acid sequence of SC_2092 that this putative protein was highly similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…An early study suggested that the loss of surface O-antigen inhibits the swarming motility of Salmonella Typhimurium because it generally acts to increase the surface “wettability” required for bacterial colony expansion (Toguchi et al, 2000 ). Recent reports demonstrated that auto-aggregation and a defect in flagellar expression were responsible for the reduced swimming motility of a Salmonella Choleraesuis rough strain with a wzx gene deletion (Zhou et al, 2014 ), and the inactivation of genes involved in LPS synthesis decreases flagellar protein production in Salmonella Typhimurium (Liu et al, 2016 ). Thus, whether a similar mechanism for defective swimming motility occurs in the Salmonella Δ rfbN mutant and whether expression of the Salmonella Newport O-antigen has an adverse effect on flagellar expression still need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study suggested that the loss of surface O-antigen inhibits the swarming motility of Salmonella Typhimurium because it generally acts to increase the surface “wettability” required for bacterial colony expansion (Toguchi et al, 2000 ). Recent reports demonstrated that auto-aggregation and a defect in flagellar expression were responsible for the reduced swimming motility of a Salmonella Choleraesuis rough strain with a wzx gene deletion (Zhou et al, 2014 ), and the inactivation of genes involved in LPS synthesis decreases flagellar protein production in Salmonella Typhimurium (Liu et al, 2016 ). Thus, whether a similar mechanism for defective swimming motility occurs in the Salmonella Δ rfbN mutant and whether expression of the Salmonella Newport O-antigen has an adverse effect on flagellar expression still need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella Typhimurium mutant strains were constructed by allelic exchange using the suicide vector pRE112, which carries a chloramphenicol resistance gene and the sucrose-sensitivity gene sacB (Edwards et al, 1998 ), a gift from Dieter Schifferli (Addgene plasmid #43828), as previously described (Zhou et al, 2014 ). To delete the rfbN gene, the primer pairs D rfbN -1F/D rfbN -1R and D rfbN -2F/D rfbN -2R were used to amplify the regions ~400 bp upstream and downstream of the ATCC14028 genome, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…O antigen is necessary for effective swimming and swarming motility in many bacteria [110][111][112][113][114][115][116][117][118][119][120], which has been demonstrated in genetic studies that investigated the effect on motility when genes involved in various steps of the O antigen synthesis and assembly pathway are deleted. Our group reported the phenotypes of several such mutants in P. aeruginosa.…”
Section: The Role Of Lps In Planktonic and Biofilm Modes Of Growthmentioning
confidence: 99%
“…The auto-aggregation assay was performed based on the method previously described by Zhou et al [ 18 ]. Briefly, Salmonella cultures were statically grown in 5 ml LB medium at 37 °C for 16 h in test tubes.…”
Section: Methodsmentioning
confidence: 99%